2020
DOI: 10.1186/s42836-020-00027-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oral and intravenous tranexamic acid in total hip arthroplasty: a systematic review and meta-analysis

Abstract: Background: Total hip arthroplasty is associated with substantial blood loss which can lead to postoperative anemia. The purpose of this systematic review and meta-analysis was to compare efficacy and safety of oral tranexamic acid (TXA) and intravenous TXA. Methods: PubMed, EMBASE, and Cochrane Library were searched from inception until December 2019. A combined searching strategy of subject words and random words was adopted. Only clinical randomized controlled trials were included. The comparisons were made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…The systematic review and meta-analysis of Qi et al compared the efficacy and safety of oral and IV TXA with 5 RCTs. They showed no significant differences between the oral and IV TXA in total blood loss, transfusion rate, or thromboembolic events 60 . Our findings are consistent with previous meta-analyses and systematic reviews.…”
Section: Discussionmentioning
confidence: 90%
“…The systematic review and meta-analysis of Qi et al compared the efficacy and safety of oral and IV TXA with 5 RCTs. They showed no significant differences between the oral and IV TXA in total blood loss, transfusion rate, or thromboembolic events 60 . Our findings are consistent with previous meta-analyses and systematic reviews.…”
Section: Discussionmentioning
confidence: 90%
“…A population‐based study including 153,169 hip fracture patients reported that the application of TXA decreased 17% of blood transfusion rates and did not increase the risk of perioperative complications, However, the optimal route of TXA administration remain unclear. Compared with traditional intravenous (IV) use of TXA, oral application has been investigated in recent studies 11–13 . A randomized clinical trial including 100 patients undergoing THA suggested oral application of TXA have same efficacy in reducing perioperative blood loss compared with IV (863.3 ± 272.5 mL vs 886.1 ± 200.2 mL, p = 0.66).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional intravenous (IV) use of TXA, oral application has been investigated in recent studies. 11 , 12 , 13 A randomized clinical trial including 100 patients undergoing THA suggested oral application of TXA have same efficacy in reducing perioperative blood loss compared with IV (863.3 ± 272.5 mL vs 886.1 ± 200.2 mL, p = 0.66). Some studies have studied the IV and local use of TXA in elderly femoral neck fracture patients, 14 , 15 while effectiveness and safety of oral application remain unclear.…”
Section: Introductionmentioning
confidence: 99%